Új módszer a gazdasági tér agrárszempontok szerinti felosztására - Fehér, Alajos (Tér és Társadalom, 1996)
The objective of the essay, besides inter- and multi-disciplinary regional research, is to expand the agrarian-based division methods of the economic spaces and to introduce a scientifically established new method. After taking a short look at the basic concepts, we deal in more details with the special features of the agricultural space of Northern Hungary, with special regard to the challenges of agriculture in the region and the responses of the agricultural producers. Within the geographical and economic space of the macro-region, we designated the areas with unfavourable endowments by harmonising the methods recommended for the member states of the European Union and the Hungarian statistical sources. The new spatial uníts, the districts were defined by linking the physical geographical units, the small regions by economic features, and also by homogenisation. In our researches we proved from several aspects that the index of gross income per capita is suitable for the measurement of the adaptation capabilities of the agricultural producers as well as for the indication of the level of economic development or underdevelopment. We compared the regional differences by the index system recommended for the member sates of the EU and by the gross income per capita. In the major part of the districts similar results were achieved, which proves that the unfavourable endowments and economic underdevelopment coincide in most cases. We created agro-economic districts by dividing the economic space of the region on the grounds of figures of gross income per capita in a three-year period. We found that the dominant factors shaping the differences between the districts (including the different adaptation capabilities of the agro-producers) were the unfavourable endowments, the high rate of agricultural employees and village unemployment. Considering the fact that we defined regional crises as crises of adaptation showing structural features, the listed factors are in a tight connection with the appearance and deepening of the crises. Thus the economic districts that we defined can be classified as crisis regíons or potential crisis regions from the aspect of regional crises, crisis-sensitive regions because of their economic underdevelopment and village unemployment and regions that are relatively successful in adaptation. The defined regions can be used for both modelling the effects of agricultural policy and the completion of regional agrarian strategies and development plans.